Growth Pattern and Feeding Habits of Snakehead Fish (Channa striata Bloch, 1793) in TelukPetai Lake, Kampar Regency, Riau Province - Mediatrix Deviani Sinaga; Eddiwan Eddiwan; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractResearch of the relationship between growth pattern and feeding habits of snakehead fish (Channa striata) was conducted in November-December 2020. This study aims to determine the growth pattern and feeding habits of snakehead fish. he method used in this research is a survey method. Fish samples were caught using bamboo fish trap in Teluk Petai Lake, Kampar Regency, Riau Province. Catching fish is carried out every two weeks with 4 replications. The sample consisted of 88 fish, 50 male and 38 female. The gravimetric method was used to observe the eating habits of snakehead fish. Meanwhile, to determine the percentage of the largest amount of food in the stomach of the fish used the IP (Index of Preponderance) method. The results of the analysis of the growth pattern of snakehead fish are allometric positive (b = 3.059).Meanwhile, the analysis of feeding habits shows that snakehead fish are classified as carnivore fish with the main food being fish (IP 75.28%), insects (IP 20.64%) and plants (IP 4.07%). Keywords: Feeding habits, Gravimeritc, Growth Pattern,Index Of Preponderance, Snakehead fish.